A Modified Penman-monteith Model for Simulating Transpiration of Citrus Trees under Water Stress - GAO Wenjie; DONG Xiaohua; ZHAO Wenyi; LI Lu; MA Yaoming; XIA Zhikai (Guan'gai paishui xuebao, 2023)
【Objective】 Transpiration is not only an important hydrological process but also a footprint of primary productivity of terrestrial systems under different environments. Its calculation at large scale is challenging. This paper proposes a method to fill this gap. 【Method】 The method is based on the modified Penman-Monteith (PM) model. The canopy resistance in the model is estimated using soil moisture based on the Ortega-Farias model, and the hydrodynamic resistance is calculated by two methods: one is based on wind speed and canopy temperature-environment relationship, and the other one is the Perrier logarithm method. The model was applied to simulate transpiration of citrus trees under water stress from June to July in 2022; its accuracy was evaluated against ground-true data. 【Result】 Water stress significantly reduced stomatal conductance and transpiration of the citrus trees. The canopy resistance estimated by the Ortega-Farias model agreed with the measured data with R2 = 0.63, accurately capturing the diurnal variation in canopy resistance under water stress. The aerodynamic resistance calculated by the leaf-based method was significantly greater than estimated by the Perrier logarithmic method. The accuracy of aerodynamic resistance calculated by the Perrier logarithmic method varied with soil water content, and the R2 between the measured and calculated transpiration from the PM model decreased from 0.66 when the plant was under slight water stress to 0.2 when the plant was under severe stress. In contrast, for the transpiration calculated using the aerodynamic resistances estimated by the leaf-simulation method, the R2 decreased from 0.71 to 0.24 with the increase in water stress. 【Conclusion】 When the soil moisture was greater than 50% of the field capacity, using the Ortega-Farias model to estimate canopy resistance and the leaf-based method to estimate aerodynamic resistance can improve the accuracy of the PM model for simulating transpiration of the citrus trees under water stress.